Paroxysmal Atrial Fibrillation: Dynamics of The Main Antioxidant Enzymes - Superoxide Dismutase and Catalase - Negreva Mariya N. (Folia Medica, 2014)
INTRODUCTION: Researchers have a particularly strong interest in the mechanisms implicated in the clinical manifestation of atrial fibrillation.